Da palhaçaria à pedagogia: uma etnografia sobre os efeitos do riso na sala de aula - Ferreira, João Victor Ramos (2021)
This research investigates the participation of laughter and humor in the classroom. The objective of the investigation was, through an experimental ethnography in the context of educational background, to research the implications of the laughter and comic in teaching and learning processes. For this, an ethnographic research was done in the Anthropology of Education classes, in the Pedagogy course of Universidade Federal do Ceará (UFC), in which participation and observation were developed, field diaries produced and ethnographic documents (diaries and students’evaluations) were catalogued. The results of the investigation underline the capacity of laughter as a revealer of culture and prejudices, thus being able to contribute to the objectives of the anthropology of education. The conclusions point to humor as a communicational and pedagogical device in the classroom, which would aim not only to collaborate with the bond between teacher and students – softening the hierarchies in the classroom – but also to help with the exercise of a sense of strange with the culture’s familiarity, the relativization of ethnocentrism and reflexivity.